Product Placement of Samsung Galaxy Note 5 in “Ariana Grande-Focus” Music Video - Putra Yunior Poela (Institute of Research and Community Outreach - Petra Christian University, 2021)
Product placement is one of popular advertisement methods, which, broadly, compile different purposes from two or more parties into one project then achieve each of parties’ purpose. Samsung is one of many companies that use the method. Samsung launched Samsung Note 5 and advertised it through a music video from Ariana Grande’s song “Focus”. Samsung chose it because by that time Ariana Grande is one of the great musicians that has a lot of fans, where Ariana Grande also launched her new music video of her song. This study has a purpose to identify how both kinds of expressions in the music video, verbal expressions and nonverbal expressions, can collaborate as the union to be used as product placement for an advertisement, in this case is product placement of Samsung Galaxy Note 5 in “Ariana Grande-Focus'' Music Video. The data in this study include the lyrics of the music and the scene capture of the music video. In fact, many aspects and details are important to put in to be elaborated as advertisement, which are divided into two types as well, verbal and nonverbal expressions. At the end it is successfully advertised. Keywords: semiotics, product placement, verbal communication, nonverbal communication, music video, advertisement